Analisis Keutungan Dan Manajemen Risiko Pada Pertenakan Ayam Potong PAM: Studi Kasus dengan Pendekatan Kualitatif Deskriptif - Binti Salisatul Mahbubah; Annisa Fitri Nurhayati; Nastiti Handayani; Naila Lutfiani; Esty Apridasari (Indo Publishing, 2026)
The livestock industry is important because it helps provide food and helps people in the community earn more money. Broiler chicken farming is a type that is in great demand because it helps provide a lot of animal protein. This study looks at how much money the business makes, finds out what risks it faces, and checks the ways it handles those risks at PAM Broiler Chicken Farm. The study used a descriptive qualitative method and focused on a case study approach. Data was gathered using detailed interviews, written records, and direct observation in the field. The results show that how efficiently it manages its productions costs, especially feed costs, which make up the biggest part of all the expenses involved in production. The farm has different problems to deal with, like issues with producing enough, changes in prices, and health problems with the chickens. To reduce possible losses, the farm uses risk management methods like choosing good quality chicks, following biosecurity practices, giving regular vaccinations, checking the health of animals, and working closely with suppliers and buyyers. The study says that good risk management helps a business stay sustainable and helps a business stay sustainable and helps make sure profits remain steady. Being able to spot, check, and manage risks is really important for keeping broiler farming business running well over a long time.